IMPACT OF THE STATE SOCIAL POLICY ON THE ECONOMIC GROWTH RATE - A. N. Ryahovskaya (Стратегические решения и риск-менеджмент)
As a result of the global financial and economic crisis, social problems have sharpened significantly. They affect the interest of the most population of the country. The efficiency of anti-recessionary measures and their productivity in the social field are analyzed in the article. According to the adjusted estimates of the RF Government, decrease in actual income of the people will continue and only by the end of 2012 a growth by only 3% to 2008 level is projected. The degree of elaboration and scientific justification of the state turnaround policy are getting special significance.